TATA BAHASA SEBAGAI CERMINAN NILAI IDEOLOGIS WACANA POLITIK PEREMPUAN DALAM “KOLOM PEREMPUAN”: KAJIAN ANALISIS WACANA KRITIS ATAS TEKS DI HARIAN SUARA MERDEKA - Muhamad Muhajir (Fakultas Adab dan Humaniora UIN Raden Fatah, 2018)
Critical Discourse Analysis is one of the language studies to uncover certain ideology particularly gender ideology. This research aimed to find out the language choice from the text writer both lexically and grammatically based on the experiential meaning. In addition, it aims to figure out the ideological value contained in discourse text. The data used in this research are 23 clauses in which there are woman words. The data were analyzed by using Critical Discourse Analysis (description, interpretation, and explanation) and Systemic Functional Linguistics approach. The data collection method was used documentation method with non-participatory observation and note-taking techniques. The data were analized by using content analysis method with abductive inferential technique. The result of this research shows that the reflected ideology based on lexical is revealed through the classification pattern (reality depiction), struggled for-ideology words, rewording (showing equality), meaning relation, and metaphor (picturing reality using symbol). In addition, the reflected ideology based on the grammatical is indicated by transitivity namely material process (projecting agent without goal, and target of action and policies), exixtential process (patriarchy bound), nominalization and passivation (hiding agent to cover actors), and negative sentence (defense on woman nature and condition). Then The structure text is analytical exposition consisting of thesis, argumentation, elaboration, and reiteration. Key words: experiential meaning, SFL, CDA, ideology